Conserved effects and altered trafficking of Cetuximab antibodies conjugated to gold nanoparticles with precise control of their number and orientation. Issue 18 (27th April 2017) - García-Fernández, Lorena; Garcia-Pardo, Javier; Tort, Olivia; Prior, Ian; Brust, Mathias; Casals, Eudald; Lorenzo, Julia; Puntes, Victor F.
Abstract : Conjugation of Cetuximab to gold nanoparticles with precise control allows tuning antibody activity, increasing its efficacy while also prolonging its effect over time. Abstract : Gold nanoparticles (17 nm) have been functionalized with the antiangiogenic monoclonal antibody drug Cetuximab at a well-defined orientation and coverage density of antibodies. Functionalization has been carried out through site-directed chemistry via the selective oxidation of the carbohydrate moiety of antibodies linked to a thiolated hydrazide. A431 tumor cells have been exposed to these conjugates for in vitro evaluation of their effects. In addition to epithelial growth factor receptor blocking, trafficking and signaling alterations were also observed. Thus, the blocking effects of Cetuximab were increased and sustained for a longer time when associated with the nanoparticles. Enhancing antibody therapy effects by decreasing the needed dose and prolonging its effect by avoiding receptor recycling may serve to obtain increased therapeutic benefits for immunotherapy.